Determinants of stock market performance in Singapore / Intan Shahira Nasarudin - Nasarudin, Intan Shahira (Faculty of Business Management, University Teknologi MARA, 2018)
Stock market is one of significants to a market economy as it provides source of income to companies, an ownerships and future gains to the investors. The research is made to study the determinants of stock market performance in Singapore. Time series data is used to run the investigation from January 201 1 until December 2017 which is on monthly basis. The tests included in this study are descriptive analysis, normality test, correlation test, unit root test and multiple regressions. Next, the determinants that listed in this study are consist of inflation rate, exchange rate, money supply, gold price and crude oil price. The findings is significant associated between the exchange rate. However, there are insignificant relationships for crude oil price, gold price, inflation rate and money supply with Singaporean stock market performance.